Inverter Performance Comparison On Solar Panel Applications - Riya Mustikasari; Muhammad Jazuli Shubhi; Langlang Gumilar; Sujito Sujito; Aripriharta Aripriharta (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2023)
In this study, the effects of harmonics on the quality of the electrical power produced by both types of inverters are compared in solar panel applications between pure sine wave and modified sine wave inverters. Additionally, a number of prior investigations into harmonics and inverters have been analyzed. This study was done to find the best kind of inverter to use with solar panels in order to increase the effectiveness and caliber of the electricity generated. Experimental research methodology is applied, with measurements of the electrical power quality produced by both types of inverters under the identical circumstances. According to the findings, the modified sine wave inverter has a higher THD power quality than the pure sine wave inverter. The modified sine wave's displacement power factor (DPF) cannot be more than one (one), but the pure sine wave's DPF is equal to the cos phi value. At a 200W load, the pure sine wave inverter has a power efficiency of 93.35% while the modified sine wave inverter has an efficiency of 81.50%. Given that modified sine waves have a higher harmonic influence, it may be said that pure sine wave inverters create electrical power of a higher quality. Therefore, it is highly advised to utilize a pure sine wave inverter for solar panel applications.